Modified glass microspheres and preparation method and application thereof
By forming a polyurea cladding layer on the surface of hollow glass microbeads, the problem of the corrosion resistance of epoxy zinc-rich primer deteriorates after increasing the amount of glass microbeads, and the breakage rate of glass microbeads is reduced, achieving efficient coating and good corrosion resistance, and reducing construction costs.
Patent Information
- Application Number
- CN202311086247.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-08-28
AI Technical Summary
After increasing the amount of glass microbeads, the corrosion resistance of existing epoxy zinc-rich primers becomes worse, and the crushing rate of glass microbeads is high in high pressure airless spraying process, resulting in a decrease in the actual coating area and increasing construction costs.
By forming a polyurea cladding layer on the surface of hollow glass microbeads and containing a small amount of unreacted isocyanate groups in the polyurea layer, the modified glass microbeads form a good combination with the epoxy resin, improving the corrosion resistance of zinc-rich primer and reducing the breakage rate of glass microbeads.
Modified glass microbeads have good acid corrosion resistance in zinc-rich primer, and the crushing rate is less than 5% during high-pressure spraying, which shortens the gap between the actual coating area and the theoretical coating area and reduces construction costs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of application of hollow glass microspheres, and in particular to modified glass microspheres and a preparation method and application thereof. Background Art
[0002] Epoxy zinc-rich primer is a commonly used anti-corrosion coating. Many steel structures at home and abroad use epoxy zinc-rich primer as anti-corrosion coating, for example: the main hall of the Beijing Olympic Games, Beijing Airport Expansion, Shanghai Pudong Airport, the main hall of the Sydney Olympic Games, the main hall of the Athens Olympic Games, etc. all use epoxy zinc-rich primer as the primer coating for anti-corrosion construction. There are also many modern new steel structure bridges that widely use epoxy zinc-rich primer as primer coating.
[0003] Epoxy zinc-rich primer is made of epoxy resin and zinc powder as the main raw materials. In my country's standard for zinc-rich primer HG / T3668-2020 "Zinc-rich Primer", the zinc content is required to be 60-80%. However, zinc has a high density and high cost. In order to achieve better results, the primer film thickness is usually increased, which will also increase the cost. At this time, glass beads can be added to the paint to reduce its cost, but when the amount of glass beads increases to a certain amount, its corrosion resistance will deteriorate. Since the resin content in epoxy zinc-rich primer is relatively small, its volume content will be significantly reduced after adding glass beads. When the glass bead content exceeds a certain amount, such as when the volume ratio of glass beads in the paint film is more than 30%, when epoxy wraps the glass beads, the amount of resin between the glass beads and adjacent glass beads or zinc powder will be significantly reduced, resulting in water and corrosive chloride ions being more easily penetrated into the surface of the glass beads when the paint surface is damaged. The interfacial bonding force between the glass bead surface and epoxy is relatively poor, and unlike zinc powder, it does not have a chemical reaction principle during the anti-corrosion process, resulting in a large amount of corrosive substances being easily adsorbed on the surface of the glass beads, but at the same time, due to the thin epoxy layer around it, the corrosive substances are easily migrated to other locations, so that when the glass beads exceed a certain amount, the corrosion resistance of the zinc-rich primer deteriorates.
[0004] To this end, the applicant disclosed in Chinese invention patent application CN 115537100 A an epoxy zinc-rich primer containing conductive polyaniline-coated hollow glass microspheres, which includes, by weight, 10 to 20 parts of epoxy resin, 3 to 10 parts of conductive polyaniline-coated hollow glass microspheres, and 40 to 60 parts of zinc powder. In this way, by adding a certain amount of conductive polyaniline-coated hollow glass microspheres to the epoxy zinc-rich primer, a conductive bridge can be formed between the upper zinc powder and the bottom zinc powder, so that the zinc powder deposited at the bottom is activated, and the cathodic protection effect of the zinc powder in the epoxy zinc-rich primer is fully exerted, thereby greatly improving the utilization rate of the zinc powder and improving the corrosion resistance of the zinc-rich primer.
[0005] Although the conductive polyaniline-coated hollow glass microspheres in the above-mentioned invention patent application can significantly enhance the bonding strength between the hollow glass microspheres and the resin matrix, and effectively avoid the floating problem caused by the low density of the hollow glass microspheres, when the hollow glass microspheres used in the epoxy zinc-rich primer are of higher density, more hollow glass microspheres need to be added to increase the coating rate; if the zinc-rich primer prepared using low-density hollow glass microspheres (Shenglait HL15, HL20 models) is used in the high-pressure airless spraying process, the actual coating area decreases compared with the theoretical coating area, and the overall cost cannot be controlled to the minimum. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a modified glass microsphere and a preparation method and application thereof. The hollow glass microsphere is modified to form a polyurea coating layer on the surface, so that the surface has a good corrosion resistance effect and can also form a good combination with the epoxy resin, thereby making the zinc-rich primer have a good corrosion resistance effect, and reducing the breakage rate of the glass microspheres during the high-pressure airless spraying process of the zinc-rich primer, thereby increasing the actual coating area and reducing the cost.
[0007] A modified glass microsphere comprises a hollow glass microsphere and a polyurea layer covering the surface of the hollow glass microsphere, wherein the polyurea layer contains less than 2% by mass of unreacted isocyanate groups. In the present invention, "unreacted isocyanate groups" refer to isocyanate groups that have not participated in any reaction during the formation of the polyurea layer.
[0008] Preferably, the surface of the hollow glass microsphere further includes a first zinc powder and a first anti-settling agent uniformly dispersed in the polyurea layer, and the content of the first zinc powder is 70% to 85% of the total mass of the first zinc powder, the first anti-settling agent and the polyurea layer. Zinc powder has a good anti-corrosion effect, so the first zinc powder is distributed in the polyurea layer, which can effectively improve the salt spray corrosion resistance of the modified glass microsphere. The function of the first anti-settling agent is mainly to prevent the first zinc powder from forming precipitation during the mixing process with other raw materials.
[0009] The density of the hollow glass microspheres is preferably 0.15 to 0.7 g / cm 3 The particle size D90 is preferably 10-110 μm. The particle size of the first zinc powder is preferably 400-700 mesh.
[0010] A method for preparing modified glass microspheres, comprising:
[0011] A primary modification is performed to pretreat the hollow glass microspheres with a siloxane treatment agent to obtain pretreated glass microspheres;
[0012] Secondary modification: modifying the pretreated glass microspheres with isocyanate and polyaspartic acid ester resin, so that the isocyanate and polyaspartic acid ester resin are polymerized on the surface of the hollow glass microspheres to form a polyurea layer;
[0013] Wherein, the siloxane treating agent is aminopropyltrimethoxysilane, aminopropyltriethoxysilane or a combination of the two, the isocyanate is HDI, IPDI or a combination of the two, and the molar ratio of the isocyanate group of the isocyanate to the amino group in the polyaspartic acid ester resin is 100: (90-95).
[0014] Based on the above, the hollow glass microspheres in the first modification step and the pretreated glass microspheres in the second modification step are always in a rotating state.
[0015] Based on the above, the first modification step includes: uniformly mixing the first solvent, the catalyst and the siloxane treatment agent to form a second mixed liquid, spraying the second mixed liquid on the surface of the hollow glass microspheres, so that the siloxane treatment agent reacts with the silanol groups on the surface of the hollow glass microspheres to obtain the pretreated glass microspheres. Preferably, the mass ratio of the hollow glass microspheres to the siloxane treatment agent is (200-400): (2-4). The mass ratio of the total mass of the isocyanate and the polyaspartic acid ester resin to the pretreated hollow glass microspheres is preferably (1-2): 12.
[0016] Based on the above, the secondary modification step includes: uniformly mixing the isocyanate, polyaspartic acid ester resin and the second solvent to form a third mixed liquid; spraying the third mixed liquid on the surface of the pretreated glass microspheres to allow the isocyanate and the polyaspartic acid ester resin to undergo a polymerization reaction, forming a polyurea layer on the surface of the pretreated hollow glass microspheres, and obtaining the modified glass microspheres.
[0017] Based on the above, the third solution also includes a uniformly mixed first zinc powder and a first anti-settling agent, and the first zinc powder accounts for 70% to 85% of the total mass of the isocyanate, polyaspartic acid ester resin, the first zinc powder and the first anti-settling agent.
[0018] The present invention also provides an application of the modified glass microspheres in zinc-rich primers. The volume ratio of the modified glass microspheres is preferably 30%-40%. The "volume ratio of modified glass microspheres" in the following of this application refers to: the ratio of the total volume of the modified glass microspheres to the total volume of non-volatile substances in the zinc-rich primer formula.
[0019] The zinc-rich primer is composed of component A and component B uniformly mixed in a mass ratio of 5 to 16: 1, wherein the component A includes the following raw materials in parts by mass: 150 to 200 parts of epoxy resin, 260 to 700 parts of second zinc powder, 25 to 40 parts of the above-mentioned modified glass microspheres, 3 to 8 parts of the second anti-settling agent, and 16 to 30 parts of the third solvent;
[0020] Group B includes the following raw materials in parts by weight: 100 parts of epoxy curing agent and 1 to 3 parts of curing accelerators.
[0021] Among them, except for the modified glass beads, other raw materials in the above-mentioned zinc-rich primer, such as epoxy resin, anti-settling agent, epoxy curing agent, curing accelerator, third solvent, etc., are all existing raw materials.
[0022] Therefore, the modified glass microspheres and the preparation method and application thereof provided by the present invention are mainly composed of hollow glass microspheres and a polyurea layer covering the surface thereof, and the polyurea layer contains a small amount of unreacted isocyanate groups. The polyurea layer makes the surface of the hollow glass microspheres have a good corrosion resistance effect. At the same time, the unreacted isocyanate groups in the polyurea layer react with the epoxy resin, which not only enhances the interfacial bonding strength between the hollow glass microspheres and the epoxy resin, but also prevents corrosive chloride ions from gathering on the surface of the glass microspheres, and has a good barrier performance for chloride ions. In particular, when the first zinc powder is distributed in the polyurea layer, the zinc-rich primer with a volume ratio of the modified glass microspheres reaching more than 30% still has a good acid salt corrosion resistance effect when its paint film is damaged. The polyurea layer has good anti-corrosion properties and good flexibility, which enables the modified glass beads to basically withstand the high pressure in the high-pressure airless sprayer with little breakage, greatly reducing the breakage rate of hollow glass beads, and the breakage rate is less than 5%, thereby shortening the gap between the actual coating area and the theoretical coating area of the zinc-rich primer and reducing construction costs. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described in detail below through specific implementation methods.
[0024] The present invention provides a modified glass microsphere, comprising a hollow glass microsphere and a polyurea layer covering the surface thereof, wherein the polyurea layer contains a small amount of unreacted isocyanate groups. Preferably, the mass proportion of the unreacted isocyanate groups in the polyurea layer is less than 2%. More preferably, the mass proportion of the unreacted isocyanate groups in the polyurea layer is less than or equal to 1%, such as 0.5%, 0.8%, etc.
[0025] Preferably, the thickness of the polyurea layer is 0.4-0.8 micrometers, such as 0.45 micrometers, 0.55 micrometers, 0.6 micrometers, 0.65 micrometers, 0.8 micrometers, etc.
[0026] Preferably, the surface of the hollow glass microsphere further includes a first zinc powder and a first anti-settling agent uniformly dispersed in the polyurea layer, and the content of the first zinc powder is 70% to 85% of the total mass of the first zinc powder, the first anti-settling agent and the polyurea layer, such as 70%, 72%, 75%, 76%, 77%, 78%, 80%, 82%, 85%, etc. More preferably, the content of the first zinc powder is 75% of the total mass of the zinc powder and the polyurea layer.
[0027] The density of the hollow glass microspheres is preferably 0.15 to 0.7 g / cm 3 , e.g. 0.15 g / cm 3 , 0.2 g / cm 3 , 0.3 g / cm 3 , 0.4 g / cm 3 , 0.5 g / cm 3 , 0.6 g / cm 3 , 0.7 g / cm 3 More preferably, the density of the hollow glass microspheres is 0.15 to 0.3 g / cm 3 The particle size D90 of the hollow glass microspheres is preferably 10 to 110 μm, such as 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 65 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, etc. More preferably, the hollow glass microspheres are HL15, HL20, etc. of Saint-Laite.
[0028] The particle size of the first zinc powder is preferably 400-700 mesh, such as 400 mesh, 450 mesh, 500 mesh, 550 mesh, 600 mesh, 650 mesh, 700 mesh, etc. The first anti-settling agent is mainly used to ensure that the first zinc powder is evenly dispersed in the third solution without forming precipitation. Therefore, the first anti-settling agent is preferably organic bentonite, castor oil derivatives, polyamide wax or any combination thereof.
[0029] The present invention also provides a method for preparing the modified glass microspheres, comprising:
[0030] One-time modification, first pre-treating the hollow glass microspheres with a siloxane treatment agent to obtain pre-treated glass microspheres, wherein the siloxane treatment agent is aminopropyl trimethoxysilane, aminopropyl triethoxysilane or a combination of the two, and the siloxane treatment agent is aminopropyl trimethoxysilane, aminopropyl triethoxysilane or a combination of the two;
[0031] Secondary modification: re-using isocyanate and polyaspartic acid ester resin to modify the pre-treated glass microspheres, so that the isocyanate and polyaspartic acid ester resin are polymerized on the surface of the hollow glass microspheres to form a polyurea layer.
[0032] Preferably, during the entire preparation process of the modified glass microspheres, the hollow glass microspheres are always in a rotating state, that is, in the above-mentioned primary modification and secondary modification steps, the hollow glass microspheres are always in a rotating state, and the rotation speed is preferably 6 to 12 r / min, such as 6 r / min, 7 r / min, 8 r / min, 9 r / min, 10 r / min, 11 r / min, 12 r / min, etc.
[0033] Among them, the main function of the siloxane treatment agent is to first react with the hydroxyl groups on the hollow glass microspheres, graft to the surface of the hollow glass microspheres, and then react with the subsequent isocyanate, so that the subsequently formed polyurea layer can be firmly formed on the surface of the glass microspheres, thereby enhancing the bonding strength between the hollow glass microspheres and the polyurea layer; in this way, the siloxane treatment agent only needs to form a uniform layer on the surface of the hollow glass microspheres, and the coating layer does not need to be very thick; therefore, preferably, the mass ratio of the hollow glass microspheres and the siloxane treatment agent is (200-400): (2-4), such as 200:2, 200:3, 200:4, 300:2, 300:4, 400:2, 400:3, etc.
[0034] The isocyanate is preferably HDI, IPDI or a combination of the two. Preferably, the solid content of the polyaspartic acid ester resin is not less than 95%, the active hydrogen equivalent is 230-400, and the viscosity is 800-2500 mPa•s, such as the viscosity can be 800mPa•s, 1000mPa•s, 1200mPa•s, 1400mPa•s, 1500mPa•s, 1650mPa•s, 1800mPa•s, 2000mPa•s, 2200mPa•s, 2500mPa•s, etc. The molar ratio of the isocyanate group in the isocyanate to the amino group in the polyaspartic acid ester resin is preferably 100: (90-95), such as 10:9, 100:91, 100:92, 100:94, 100:95, etc., so that the amino groups in the system fully react with the isocyanate groups, and a small amount of isocyanate groups do not participate in the reaction. The isocyanate groups that do not participate in the reaction are mainly used for subsequent reaction with epoxy resin to increase the interfacial bonding strength between the modified glass microspheres and the epoxy resin. The mass ratio of the total mass of the isocyanate and the polyaspartic acid ester resin to the pretreated hollow glass microspheres is preferably (1-2): 12, such as 1:12, 1.3:12, 1.5:12, 1.8:12, 2:12, etc., so that it is conducive to forming a polyurea layer with a thickness of 0.4-0.8 microns.
[0035] The first modification step includes: uniformly mixing the first solvent, the catalyst and the siloxane treatment agent to form a second mixed liquid, spraying the second mixed liquid on the surface of the hollow glass microspheres, so that the siloxane treatment agent reacts with the silanol groups on the surface of the hollow glass microspheres to obtain the pretreated glass microspheres. The first solvent is alcohol, toluene, xylene or any combination thereof. The catalyst is dibutyltin dilaurate or dibutyltin dichloride. The mass ratio of the glass microspheres to the first solvent is preferably (3-4): (3-5), such as 1:1, 3:4, 3:5, 3.5:3, 3.5:4, 3:5, 4:3, 4:5, etc. The mass ratio of the siloxane treatment agent to the catalyst is preferably (2-4):(0.05-0.1), such as 2:0.05, 2:0.075, 2:0.1, 3:0.05, 3:0.075, 3:0.09, 3:0.1, 4:0.05, 4:0.08, 4:0.1, etc.
[0036] Specifically, the first modification step includes: fully stirring and dispersing the first solvent and the catalyst to obtain a first mixed solution; fully stirring and dispersing the siloxane treatment agent and the first mixed solution to obtain a second mixed solution; spraying the second mixed solution on the hollow glass microspheres within 60 minutes to react the siloxane treatment agent with the silanol groups on the surface of the hollow glass microspheres to obtain the pretreated glass microspheres. Among them, the stirring speed during the preparation of the first mixed solution and the second mixed solution is preferably 1000-1500 r / min, such as 1000 r / min, 1100 r / min, 1200 r / min, 1250 r / min, 1300 r / min, 1400 r / min, 1500 r / min, etc. The stirring and dispersing time of the first mixed solution is preferably 10-15 minutes, such as 10 minutes, 12 minutes, 13 minutes, 15 minutes, etc. The stirring and dispersing time of the second mixed solution is preferably 5-10 minutes, such as 5 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, etc. The spraying time of the second mixed solution is preferably 30 to 45 minutes, such as 30 minutes, 40 minutes, and 45 minutes. The reaction temperature of the hollow glass microspheres and the siloxane treatment agent is preferably 80 to 110°C, such as 80°C, 90°C, 95°C, 100°C, 110°C, etc.; the reaction time is preferably 3 to 5 hours, such as 3 hours, 4 hours, and 5 hours.
[0037] The secondary modification step includes: uniformly mixing the isocyanate, polyaspartic acid ester resin and the second solvent to form a third mixed solution; spraying the third mixed solution on the surface of the pretreated glass microspheres, causing the isocyanate and polyaspartic acid ester resin to undergo polymerization reaction, forming a polyurea layer on the surface of the pretreated hollow glass microspheres, and obtaining the modified glass microspheres. Wherein, the second solvent is toluene, xylene, ethyl acetate, butyl acetate or any combination thereof. Specifically, the isocyanate, polyaspartic acid ester resin and the second solvent are dispersed at 1000-1500 r / min for 3-5 min to obtain the third mixed solution, spraying the third mixed solution on the surface of the pretreated glass microspheres within 30 min, causing the isocyanate and polyaspartic acid ester resin to undergo polymerization reaction at 40-60°C for 1-3 h to form the polyurea layer, and obtaining the modified glass microspheres. Wherein, the spraying time is preferably 15-20 min, such as 15 min, 20 min.
[0038] The third solution preferably also includes a uniformly mixed first zinc powder and a first anti-settling agent. The first zinc powder preferably accounts for 70% to 85% of the total mass of the isocyanate, polyaspartic acid ester resin and the first zinc powder, such as 70%, 72%, 75%, 76%, 77%, 78%, 80%, 82%, 85%, etc. More preferably, the first zinc powder accounts for 75% of the total mass of the isocyanate, polyaspartic acid ester resin and the first zinc powder. Specifically, the mass ratio of the isocyanate to the total mass of the polyaspartic acid ester resin, the first zinc powder, and the first anti-settling agent is preferably (200-250):(480-600):(3-10), such as 200:480:3, 200:500:5, 200:550:6, 200:600:8, 250:600:10, 250:600:5, 200:480:5, 200:480:8, 250:600:3, etc. The mass ratio of the total mass of the isocyanate, the polyaspartic acid ester resin, the first zinc powder and the first anti-settling agent, the pretreated glass microbeads, and the second solvent is preferably (4-6):12:(5-7.5), such as 4:12:5, 4:12:6, 4:12:7.5, 5:12:5, 5:12:6, 5:12:7, 5:12:7.5, 6:12:5, 6:12:6, 6:12:7.5, etc.
[0039] The present invention also provides an application of the modified glass microspheres in zinc-rich primers. The volume ratio of the modified glass microspheres is preferably 30% to 40%, such as 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%; more preferably, the volume ratio of the modified glass microspheres is 30% to 35%.
[0040] The zinc-rich primer is composed of component A and component B uniformly mixed in a mass ratio of 5 to 16: 1. Component A includes the following raw materials in parts by mass: 150 to 200 parts of epoxy resin, 260 to 700 parts of second zinc powder, 25 to 40 parts of the above-mentioned modified glass microspheres, 3 to 8 parts of the second anti-settling agent, and 16 to 30 parts of the third solvent; component B includes the following raw materials in parts by mass: 100 parts of epoxy curing agent and 1 to 3 parts of curing accelerator.
[0041] The preferred mass fraction of the second zinc powder is 300 to 650. The preferred mass fraction of the modified glass microspheres is 28 to 35, such as 28, 29, 30, 31, 32, 33, 34, 35, and the like.
[0042] Among them, except for the modified glass beads, other raw materials in the above-mentioned zinc-rich primer, such as epoxy resin, second anti-settling agent, epoxy curing agent, curing accelerator, third solvent, etc., are all existing raw materials.
[0043] The epoxy resin is preferably epoxy resin E-44, epoxy resin E-51 or any combination thereof. The epoxy curing agent is preferably one or more of aliphatic amine curing agents, aromatic amine curing agents and amine-modified curing agents, such as polyamide 651, 650 or T31. The curing accelerator is preferably DMP-30.
[0044] The second zinc powder and the second anti-settling agent as raw materials in the zinc-rich primer are preferably the same as the first zinc powder and the first anti-settling agent used in the modified glass microspheres.
[0045] The third solvent is one of acetone, toluene, n-butanol, xylene or dibutyl ether. The third solvent is preferably composed of n-butanol and toluene, and the mass ratio of n-butanol to methanol is preferably 6-10: 10-20, such as 6:10, 6:15, 6:20, 7:10, 7:15, 7:20, 8:10, 8:12, 8:15, 8:18, 8:20, 9:10, 9:15, 9:20, 10:10, 10:15, 10:20, etc.
[0046] Therefore, a polyurea layer is formed on the surface of the modified glass microspheres provided by the present invention. The polyurea layer has good flexibility and is coated on the surface of the hollow glass microspheres, so that the breakage rate of the glass microspheres is greatly reduced under a pressure of 6 Mpa; thereby, when the zinc-rich primer is constructed using an airless spraying technology, the breakage rate of the glass microspheres is less than 5%, such as 4%, 3%, 2%, 1%, etc.; thereby shortening the gap between the actual coating area of the zinc-rich primer and the theoretical coating area, and reducing the construction cost.
[0047] At the same time, the polyurea layer formed on the hollow glass microspheres not only has good flexibility, but also has anti-corrosion function, so that when the volume ratio of the modified glass microspheres in the zinc-rich primer exceeds 30%, the zinc-rich primer still has good anti-corrosion performance; in particular, the polyurea and the first zinc powder distributed therein make the surface of the hollow glass microspheres have good anti-corrosion effect, and can also form a good combination with the epoxy resin, so that the corrosive chloride ions do not gather on the surface of the glass microspheres. Even if the zinc-rich primer film is damaged, it has a good barrier performance against chloride ions, thereby making the zinc-rich primer have a better corrosion resistance effect.
[0048] In order to more clearly describe the technical solution of the present invention, it is described in detail through the following examples, wherein the zinc-rich primer and the modified glass microspheres contained therein provided in the following examples or comparative examples use the same zinc powder and anti-settling agent.
[0049] 1. Effect of modified glass beads on the performance of zinc-rich primer
[0050] The selection and process of hollow glass microsphere modified materials have an important influence on the performance of zinc-rich primer. The specific influences are shown below.
[0051] Embodiment S1 of the present invention provides an epoxy zinc-rich primer, which is composed of component A and component B uniformly mixed in a mass ratio of 14.3: 1; component A is composed of the following raw materials in parts by mass: 180 parts of epoxy resin E-44, 650 parts of second zinc powder with a particle size of 500 mesh, 30 parts of modified glass microspheres, 6 parts of second organic bentonite with a particle size of 95 mesh, 8 parts of n-butanol, and 15 parts of toluene; component B is composed of the following raw materials in parts by mass: 100 parts of polyamide T31 and 2 parts of curing accelerator DMP-30.
[0052] The modified glass microspheres are mainly prepared by the following steps:
[0053] The first modification is to stir and disperse the first solvent toluene and the catalyst dibutyltin dilaurate at 1300 r / min for 12 min to obtain a first mixed solution; the treatment agent aminopropyltrimethoxysilane and the first mixed solution are stirred and dispersed at 1300 r / min for 8 min to obtain a second mixed solution; firstly, the Sanlait model HL15 hollow glass microspheres are placed in a rotary furnace at a temperature of about 95°C and a rotation speed of about 8 r / min to make them in a rotating state, and then the second mixed solution is sprayed on the rotating glass microspheres within 60 min, so that the treatment agent reacts with the hollow glass microspheres for 4 h to obtain surface pretreated glass microspheres, wherein the mass ratio of the hollow glass microspheres, the treatment agent, toluene and dibutyltin dilaurate is 350:3:400:0.08;
[0054] Secondary modification, polyurea A isocyanate HDI, polyurea B component polyaspartic acid ester resin, first zinc powder, organic bentonite and second solvent ethyl acetate are stirred and dispersed at 1300 r / min for 5 minutes to obtain a third mixed solution; the pretreated glass microspheres are first placed in a rotary furnace at a temperature of about 60°C and a rotation speed of about 8 r / min to make them in a rotating state, and then the third mixed solution is sprayed on the rotating pretreated glass microspheres within 20 minutes to make HDI react with the polyaspartic acid ester resin and the pretreated glass microspheres respectively. h, forming polyurea on the surface of the glass microspheres to complete the modification of the glass microspheres and obtain the above-mentioned modified glass microspheres; wherein the ratio of the isocyanate group of HDI to the amino group in the polyaspartic acid ester resin of the polyurea B component is about 100:95, and the total mass of HDI, polyaspartic acid ester resin, the first zinc powder and the organic bentonite as raw materials of the glass microsphere modifier, the mass ratio of which, the mass ratio of the above-mentioned pretreated glass microspheres and ethyl acetate is 500:1200:650, wherein the mass ratio of the total mass of HDI and the polyaspartic acid ester resin, the first zinc powder and the organic bentonite is 200:500:6.0; the solid content of the polyaspartic acid ester resin is about 95%, the active hydrogen equivalent is 300, and the viscosity is 1600 mPa•s.
[0055] Example S2 and Comparative Examples D1-4 each provide a zinc-rich primer, which has substantially the same raw material composition and process as Example S1, except that:
[0056] The main difference between Example S2 and S1 is that Example S2 uses aminopropyltriethoxysilane to replace the treating agent aminopropyltrimethoxysilane in Example S1, and the other ingredients and processes are the same as Example S1.
[0057] The main difference between Comparative Example D1 and Example S1 is that Comparative Example D1 uses vinyltriethoxysilane as the treating agent, and the other components and processes are the same as Example S1.
[0058] Comparative Example D2 uses the same glass microsphere bulk content as in Example S1, and converts the total mass of the polyurea formed in the secondary modification of the glass microspheres into an equal amount of polyurethane, that is, the molar ratio of the isocyanate group of HDI to the hydroxyl group of the polyether YD305 in Comparative Example D2 is 100:95, and the total mass of the two is equal to the total mass of HDI and the polyaspartic acid ester resin in Example S1, and the other components and processes are the same as in Example S1.
[0059] Comparative Example D3 uses the same glass microsphere bulk content as in Example S1. In this comparative example, only the treatment agent is used to modify the glass microspheres without secondary modification. The total mass of the polyurea, the first zinc powder and the first anti-settling agent in the secondary modification process of the glass microspheres in Example S1 is converted into an equal amount of epoxy resin, the second zinc powder and the second anti-settling agent and added to the epoxy zinc-rich primer.
[0060] The difference between the use of comparative example D4 and that of example S1 is that comparative example D4 does not first modify the glass microspheres with a treating agent, but directly modifies the hollow glass microspheres with HDI, polyaspartic acid ester resin, the first zinc powder and the first anti-settling agent, and the other components and processes are the same as those of example S1.
[0061] The following performance tests were performed on the zinc-rich primers provided in Examples S1 and S2 and Comparative Examples D1 to D4, and the test results are shown in Table 1.
[0062] (1) Breakage rate test method: Use a measuring cup to measure the volume of 3 kg of epoxy zinc-rich primer S1-2 and D1-4 shown in Table 1 before and after spraying, which is sprayed into a bucket by a plunger-type high-pressure (6 MPa) airless sprayer. According to the formula (V 前 -V 后 ) / V 玻 , calculated the glass bead breakage rate, and the results are shown in Table 1.
[0063] (2) Coating area test method: 1 kg of paint is evenly sprayed onto a flat surface using a plunger-type high-pressure (6 MPa) airless sprayer. The spray thickness is between 95 μm and 100 μm, and the spray area is measured.
[0064] (3) Salt spray test: The epoxy zinc-rich primers S1-2 and D1-4 shown in Table 1 were coated on a tinplate substrate, and a paint film with a thickness of 90 μm was formed after drying. The scratch salt spray test was carried out for 1000 h in accordance with the standard HG_T 3668-2020. After the 1000 h salt spray test, the unidirectional corrosion length of the scratch without blistering, rusting, cracking, peeling, etc. was shown in Table 1. The longer the unidirectional corrosion length of the scratch, the worse the salt spray corrosion resistance of the zinc-rich primer; the shorter the unidirectional corrosion length of the scratch, the better the salt spray corrosion resistance of the zinc-rich primer.
[0065] Table 1 Effect of modified glass microspheres on the performance of epoxy zinc-rich primer
[0066]
[0067] It can be seen from Table 1 that when the volume ratio of the modified glass microspheres is 34.7%, the modified raw material treatment agent of the glass microspheres and the raw material components of the polyurea synthesis have an important influence on the performance of the zinc-rich primer. Among them, from the results of Examples S1, S2 and Comparative Example D1, it can be seen that the breakage rate and salt spray resistance of the vinyl silane coupling agent are worse than those of the aminosilane coupling agent. The main reason is that the vinyl group cannot form a good combination with the polyurea system, while the amino group in the aminosilane coupling agent can be combined with the isocyanate group, so that the pre-treated glass microspheres and the polyurea layer have a strong bonding strength, so that the modified glass microspheres can withstand high pressure and salt spray tests, so that the corresponding epoxy zinc-rich primer has a lower breakage rate and better anti-chlorine corrosion effect.
[0068] From the results of Example S1 and Comparative Example D2, it can be seen that Comparative Example D2 uses a combination of isocyanate and polyether to modify the glass microspheres, so that the corresponding zinc-rich primer has a relatively poor breakage rate and salt spray resistance; this is mainly due to the low activity of the polyether and the insufficient degree of curing of the system.
[0069] From the results of Example S1 and Comparative Examples D3 and D4, it can be seen that compared with Comparative Examples D3 and D4, which are treated with a single aminosilane coupling agent or a single polyurea synthetic raw material, respectively, Example S1 is treated with an aminosilane coupling agent first and then treated with polyurea to obtain a modified glass microsphere, and the corresponding zinc-rich primer has a relatively low breakage rate, a relatively large coating area, and a relatively good salt spray resistance effect. This is mainly because the glass microspheres modified twice in the embodiment of the present invention have a relatively strong interface bonding force between the hollow glass microspheres and the epoxy resin.
[0070] 2. Glass beads secondary modified materials for coatings
[0071] Embodiment S3 of the present invention provides an epoxy zinc-rich primer, which is composed of component A and component B uniformly mixed in a mass ratio of 8.4: 1; component A is composed of the following raw materials in parts by mass: 170 parts of epoxy resin E-51, 500 parts of second zinc powder with a particle size of 550 mesh, 33 parts of modified glass microspheres shown in Table 2, 6 parts of second organic bentonite with a particle size of 98 mesh, 8 parts of n-butanol, and 15 parts of toluene; component B is composed of the following raw materials in parts by mass: 100 parts of polyamide 651 and 2 parts of curing accelerator DMP-30.
[0072] The modified glass microspheres used in Example S3 are mainly prepared by the following steps:
[0073] The invention provides a first modification, wherein ethanol and dibutyltin dichloride are stirred and dispersed at 1300 r / min for 12 min to obtain a first mixed solution; aminopropyltrimethoxysilane and the first mixed solution are stirred and dispersed at 1300 r / min for 8 min to obtain a second mixed solution; hollow glass microspheres (model HL15 of the applicant Saint-Laite) are first placed in a rotary furnace at a temperature of about 95°C and a rotation speed of about 8 r / min to make them rotate, and then the second mixed solution is sprayed onto the rotating glass microspheres within 60 min to make aminopropyltrimethoxysilane react with the hollow glass microspheres for 4 h to obtain surface pretreated glass microspheres, wherein the mass ratio of the hollow glass microspheres, aminopropyltrimethoxysilane, ethanol and dibutyltin dichloride is 350:3:400:0.07;
[0074] Secondary modification, HDI, polyaspartic acid ester resin (solid content of about 95%, active hydrogen equivalent of 250, viscosity of 1000 mPa•s), the first zinc powder, the first organic bentonite and toluene are stirred and dispersed at 1300 r / min for 4 min to obtain a third mixed solution; the pretreated glass microspheres are first placed in a rotary furnace at a temperature of about 55°C and a rotation speed of about 8 r / min to make it in a rotating state, and then the third mixed solution is sprayed on the rotating pretreated glass microspheres within 30 minutes to make HDI react with the polyaspartic acid ester resin and the pretreated glass microspheres respectively for 3 minutes. h, forming polyurea on the surface of the glass microspheres to complete the modification of the glass microspheres and obtain the above-mentioned modified glass microspheres; wherein the binary molar ratio of the isocyanate group of HDI to the amino group of the polyaspartic acid ester resin is 100:93, the total mass of HDI, the polyaspartic acid ester resin, the first zinc powder and the first organic bentonite, the first ternary mass ratio of the pretreated glass microspheres and ethyl acetate is 500:1200:650, and the second ternary mass ratio of the total mass of HDI and the polyaspartic acid ester resin, the first zinc powder and the second organic bentonite is 200:480:6.5.
[0075] Comparative Examples D5 to D9 each provide a zinc-rich primer, which is basically the same as the raw material composition and process of Example S3, and the glass microsphere content added in each Comparative Example D5 to D9 is also the same as the glass microsphere content in Example S3, and the main difference is that the modification formula used in the secondary modification process is different, as shown in Table 2. Among them, the zinc-rich primers provided by Comparative Examples D5 to D9 and Example 3 mainly have the following differences, and other formulas and process parameters are the same:
[0076] In the secondary modification process of the hollow glass microspheres in Comparative Examples D5 and D6, the binary molar ratio of the isocyanate group of HDI to the amino group of the polyaspartic acid ester resin used was different from that in Example S3;
[0077] In the secondary modification process of the hollow glass microspheres in Comparative Example D7, the total mass of HDI and polyaspartic acid ester resin used is the same as that in Example S3, but zinc powder and organic bentonite (anti-settling agent) are not added in the secondary modification process, and the total content of zinc powder in the zinc-rich primer formula provided by Comparative Example D7 and Example S3 is equal, and the total content of organic bentonite therein is also equal;
[0078] In the secondary modification process of the hollow glass microspheres in Comparative Examples D8 and D9, the amounts of zinc powder and anti-settling agent added are different from those in Example S3, and the total contents of the first zinc powder and the second zinc powder in the zinc-rich primer formulas provided in Comparative Examples D8, D9 and Example S3 are equal, and the total contents of the first organic bentonite and the second organic bentonite are also equal.
[0079] The same method as in “I. Effect of modified glass microspheres on performance of zinc-rich primer” was used to perform performance tests on the zinc-rich primers provided in Example S3 and Comparative Examples D5 to D9, and the test results are shown in Table 2.
[0080] Table 2 Effect of modified glass microspheres on the performance of epoxy zinc-rich primer
[0081]
[0082] From the results of Example S3 and Comparative Examples D5-6, it can be seen that when the volume ratio of the modified glass microspheres is 33.1%, the ratio of the isocyanate group to the amino group used has an impact on the breakage rate, coating area and anti-corrosion effect of the glass microspheres in the zinc-rich primer. If the amino content is relatively high, it will cause incomplete polyurea curing, so that the breakage rate of the glass microspheres in the zinc-rich primer is relatively high, the coating area is small, and the salt spray resistance effect is poor, as shown in D5. If the isocyanate content is too high, the polyurea curing will also be incomplete, so that the breakage rate of the glass microspheres in the zinc-rich primer is relatively high, the coating area is small, and the salt spray resistance effect is poor, as shown in D6.
[0083] From the results of Example S3 and Comparative Examples D7 to 9, it can be seen that the zinc powder content in the modified glass microspheres has an important influence on the performance of the zinc-rich primer. When no zinc powder is added or the content is relatively low, the anticorrosion effect of the zinc-rich primer is relatively poor. As shown in D7. When the zinc powder content is relatively high, because more polyurea protective layers cannot be provided, the breakage rate of the glass microspheres in the zinc-rich primer is relatively high, and the anticorrosion effect is also relatively poor. Therefore, the content of zinc powder in the modified glass microspheres should be limited to an appropriate range.
[0084] 3. Effect of zinc powder content in zinc-rich primer on its performance
[0085] Consider the effect of the zinc powder content in the component A of the epoxy zinc-rich primer on its performance. The raw material components of the epoxy zinc-rich primer provided in Example S4 are substantially the same as those of the zinc-rich primer provided in Example S1, with the main differences being that the second zinc powder content in the component A in Example S4 is 350 parts by mass, the second anti-settling agent is 3 parts by mass, i.e., 53% of the second zinc powder content in the component A in Example S1, and the volume ratio of the modified glass microspheres is 33.7%.
[0086] After testing, the glass beads (Shenglait model HL15) in the epoxy zinc-rich primer provided in Example S4 had a crushing rate of 3% and a coating area of 7.0 m 2 In the salt spray test, the unidirectional corrosion at the scratched area after 1000 h was about 1.9 mm, and there was no blistering, rusting, cracking, peeling, etc. at the unscratched area. It can be seen that compared with the comparative example D3, the crushing rate of Example S4 is relatively low, and the salt spray test effect is basically the same; compared with Example S1, the crushing rate of Example S4 is the same, but the anti-chlorine corrosion effect is relatively poor, but it is still less than 2.0 mm, reaching the standard required by the industry.
[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A modified glass microsphere, characterized in that: The invention comprises hollow glass microspheres and a polyurea layer covering the surface thereof, wherein the polyurea layer contains unreacted isocyanate groups with a mass fraction of less than 2%, and the surface of the hollow glass microspheres further comprises a first zinc powder and a first anti-settling agent uniformly dispersed in the polyurea layer, and the content of the first zinc powder is 70% to 85% of the total mass of the first zinc powder, the first anti-settling agent and the polyurea layer. The preparation method of the polyurea layer comprises: One-time modification, using a siloxane treatment agent to perform a first modification treatment on the hollow glass microspheres to obtain pretreated glass microspheres; Secondary modification, uniformly mixing isocyanate, polyaspartic acid ester resin, a second solvent, the first zinc powder and the first anti-settling agent to form a third mixed solution; spraying the third mixed solution on the surface of the pretreated glass microspheres, so that the isocyanate and the polyaspartic acid ester resin are polymerized on the surface of the hollow glass microspheres to form the polyurea layer, and the first zinc powder and the first anti-settling agent are uniformly dispersed in the polyurea layer; Wherein, the siloxane treating agent is aminopropyltrimethoxysilane, aminopropyltriethoxysilane or a combination of the two, the isocyanate is HDI, IPDI or a combination of the two, and the molar ratio of the isocyanate group of the isocyanate to the amino group in the polyaspartic acid ester resin is 100: (90-95), the mass ratio of the hollow glass microspheres and the siloxane treating agent is (200-400): (2-4), and the mass ratio of the total mass of the isocyanate and the polyaspartic acid ester resin to the pre-treated hollow glass microspheres is (1-2):
12.
2. A method for preparing the modified glass microspheres according to claim 1, comprising: One-time modification, using a siloxane treatment agent to perform a first modification treatment on the hollow glass microspheres to obtain pretreated glass microspheres; Secondary modification: uniformly mixing isocyanate, polyaspartic acid ester resin, a second solvent, a first zinc powder and a first anti-settling agent to form a third mixed solution; spraying the third mixed solution on the surface of the pretreated glass microspheres to polymerize the isocyanate and the polyaspartic acid ester resin on the surface of the hollow glass microspheres to form a polyurea layer, and the first zinc powder and the first anti-settling agent are uniformly dispersed in the polyurea layer; The siloxane treatment agent is aminopropyltrimethoxysilane, aminopropyltriethoxysilane or a combination of the two, the isocyanate is HDI, IPDI or a combination of the two, and the molar ratio of the isocyanate group of the isocyanate to the amino group in the polyaspartic acid ester resin is 100: (90-95), the mass ratio of the hollow glass microspheres to the siloxane treatment agent is (200-400): (2-4), the mass ratio of the total mass of the isocyanate and the polyaspartic acid ester resin to the pretreated hollow glass microspheres is (1-2): 12, and the first zinc powder accounts for 70% to 85% of the total mass of the isocyanate, the polyaspartic acid ester resin, the first zinc powder and the first anti-settling agent.
3. The preparation method according to claim 2, characterized in that: The hollow glass microspheres in the first modification step and the pretreated glass microspheres in the second modification step are always in a rotating state.
4. The preparation method according to claim 2 or 3, characterized in that: The first modification step includes uniformly mixing the first solvent, the catalyst and the siloxane treatment agent to form a second mixed solution, spraying the second mixed solution on the surface of the hollow glass microspheres, allowing the siloxane treatment agent to react with the silanol groups on the surface of the hollow glass microspheres to obtain the pretreated glass microspheres.
5. The preparation method according to claim 2 or 3, characterized in that: The secondary modification step comprises: dispersing the isocyanate, polyaspartic acid ester resin, the second solvent, the first zinc powder and the first anti-settling agent at 1000-1500 r / min for 3-5 minutes to obtain the third mixed solution; spraying the third mixed solution on the surface of the pretreated glass microspheres within 30 minutes, polymerizing the isocyanate and the polyaspartic acid ester resin at 40-60° C. for 1-3 hours, forming the polyurea layer on the surface of the pretreated hollow glass microspheres, and obtaining the modified glass microspheres.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the total mass of the isocyanate and the polyaspartic acid ester resin, the first zinc powder, and the first anti-precipitation agent is (200-250): (480-600): (3-10); the mass ratio of the total mass of the isocyanate, the polyaspartic acid ester resin, the first zinc powder and the first anti-precipitation agent, the pretreated glass microbeads, and the second solvent is (4-6): 12: (5-7.5).
7. Use of the modified glass microspheres according to claim 1 in zinc-rich primer.
8. The use according to claim 7, wherein the zinc-rich primer is composed of component A and component B uniformly mixed in a mass ratio of 5 to 16: 1, wherein: The component A comprises the following raw materials in parts by mass: 150-200 of epoxy resin, 260-700 of second zinc powder, 25-40 of the above-mentioned modified glass microspheres, 3-8 of the second anti-settling agent, and 16-30 of the third solvent; Group B includes the following raw materials in parts by weight: 100 parts of epoxy curing agent and 1 to 3 parts of curing accelerators.
Citation Information
Patent Citations
Preparation method and application of hollow glass bead modified polyaspartic acid ester
CN113912840A
Epoxy zinc-rich primer containing conductive polyaniline coated hollow glass beads and preparation method of epoxy zinc-rich primer
CN115537100A